Aspects to Consider for a More Useful, Discriminative Predictive Tool for CAP Mortality in T2DM [Letter] - Geltser D (Dove Medical Press, 2021)
Dan Geltser Imperial College London, School of Medicine, London, UKCorrespondence: Dan Geltser Email dg1116@ic.ac.uk I read with great interest the paper by Ma et al1 which explored the sensitivity and specificity of using CURB-65 and the PSI scoring systems to predict mortality in type 2 diabetes mellitus (T2DM) patients with community-acquired pneumonia (CAP). The study importantly identified the need for a more specific prediction model in T2DM cohorts. CAP accompanied with T2DM commonly presents in both primary care and the ED and as a 5th-year medical student I would like to highlight other factors which should be discussed when considering the conclusion and aid the development of a more useful, discriminative tool for the diagnosis and prognosis of CAP in T2DM.   View the original paper by Ma and colleagues